Digital Leadership (Theory and Implementation in Higher Education) - Rizki, Agam Muhammad; Suwadi, Suwadi (Jurnal Ekonomi, 2024)
This article is oriented to examine digital leadership theory and the implementation of digital leadership in higher education. The research method used is library research with a qualitative approach. The analysis used is content analysis or content from sources related to digital leadership in higher education. The research results show that (1). Leadership theory in the context of higher education is becoming increasingly important along with technological developments and the need for rapid adaptation to digital change. There are 5 important typologies for building digital leadership in educational institutions, namely digital competence, digital culture, digital differentiation, digital governance and digital advocacy. Digital leadership also requires understanding technology, collaboration between sectors and support for innovation through real movements according to each field. (2). Implementing digital leadership in a higher education institution requires the integration of technology in learning, developing digital skills of staff and students and increasing efficiency through digital systems while still considering the data security aspects of users and those involved in digitalization.